Problems of Internal Control Organization at Enterprises of the Republic of Kazakhstan - KHUANYSH, Lena (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).13, 2018)
The relevance of the problem is conditioned by the need for the organization of internal control in commercial organizations. Indeed, both the safety of their property and cash, achievement of financial goals and objectives by the company, and the avoidance of errors in accounting and tax accounting, which ultimately lead to a distortion of financial and tax reporting, depend on internal control. Errors and inaccuracies, deliberate violations can lead to sanctions from inspection bodies or are capable of misleading the shareholders (participants) and partners of the organization in the event of a distortion of the reporting. The purpose of the article is to develop recommendations for commercial organizations of the Republic of Kazakhstan on the improvement of internal control systems based on foreign practice. The leading methods of research of this problem are: questionnaire that allows you to obtain, based on a certain sample, actual results that allow you to evaluate the development of the internal control system of the enterprises under study; modeling that allows you to create an internal control model for large trading companies. This article presents the main approaches to the organization of internal control systems used in Kazakhstan companies operating in the sphere of industrial production enterprises. Features and problems of their application are also revealed, recommendations and optimal models for improving these systems are formulated, taking into account the modern needs of the developing business. The materials of the article are of practical value to trading companies, as the presented models and recommendations for improving the internal control system are aimed at improving financial control in the business of such entities, bringing these systems closer to international standards and increasing control effectiveness (more rapid identification of errors and violations, that happen in the accounting process and financial transactions).